Flood embankments monitoring system in on-line mode = Monitorowanie wałów przeciwpowodziowych w trybie on-line - Michta, Emil; Powroźnik, Piotr; Rybski, Ryszard; Szulim, Robert; Piotrowski, Krzysztof; Kołodziejczyk, Urszula; Kostecki, Jakub (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
The chapter presents a short description of flood embankments assessing and presents the concept of a solution for the continuous monitoring of flood embankments with the use of currently available ICT technologies.
Keywords: wały przeciwpowodziowe; monitorowanie wałów przeciwpowodziowych; technologie IT